2001
DOI: 10.1006/mthe.2000.0223
|View full text |Cite
|
Sign up to set email alerts
|

Protection and in Vivo Selection of Hematopoietic Stem Cells Using Temozolomide, O6-Benzylguanine, and an Alkyltransferase-Expressing Retroviral Vector

Abstract: Transfer of drug resistance genes to hematopoietic stem cells offers the potential to protect cancer patients from drug-induced myelosuppression and to increase the number of gene-modified cells by in vivo selection. In this study, a retroviral vector expressing both a P140K variant of human O6-methylguanine-DNA methyltransferase (MGMT) and an EGFP reporter gene was evaluated for stem cell protection in a murine transplant model. Mice transplanted with vector-transduced cells showed significant resistance to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
103
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(106 citation statements)
references
References 41 publications
2
103
0
1
Order By: Relevance
“…Earlier studies of retroviral gene marking in mice may have suggested similar hypotheses, but did not allow clear conclusions, because the assessment of clonality, unique transgene copy or multilineage differentiation was incomplete or impossible due to the experimental conditions used. 7,[9][10][11][12][13][14][15][18][19][20][21][22][23][24][25]29 In contrast to the positive outcome that we observed after selection for HSCs expressing the transgene in vivo, flow cytometry-mediated sorting for high transgene expression in cultured HSCs, prior to primary BMT, did not improve long-term expression. 9 However, the loci supporting transgene expression in vitro and in vivo are not necessarily identical, because of the anticipated differences of the signals regulating survival in the recombinant environment.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Earlier studies of retroviral gene marking in mice may have suggested similar hypotheses, but did not allow clear conclusions, because the assessment of clonality, unique transgene copy or multilineage differentiation was incomplete or impossible due to the experimental conditions used. 7,[9][10][11][12][13][14][15][18][19][20][21][22][23][24][25]29 In contrast to the positive outcome that we observed after selection for HSCs expressing the transgene in vivo, flow cytometry-mediated sorting for high transgene expression in cultured HSCs, prior to primary BMT, did not improve long-term expression. 9 However, the loci supporting transgene expression in vitro and in vivo are not necessarily identical, because of the anticipated differences of the signals regulating survival in the recombinant environment.…”
Section: Discussionmentioning
confidence: 95%
“…1,3,[20][21][22][23] To improve the treatment of cancer patients, resistance would be required in all stages and lineages of norLeukemia mal hematopoiesis. In the present study, virtually all BM progenitors, mature myeloid or lymphoid cells, and even enucleated PLTs and RBCs expressed the transgenic protein following selection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Strategies for selective enrichment of donor hematopoietic stem cells to enhance engraftment were initially developed as a treatment for myelosuppression. There are many studies which have investigated various drug resistance-mediated in vivo selection enrichment strategies [7][8][9][10][11][12][13] among which, the most effective strategy uses O 6 -methylguanine-DNA-methyltransferase (MGMT) (P140K) gene-mediated drug resistance [14][15][16][17][18][19]. MGMT (P140K) is a mutant form of the drug resistance gene MGMT.…”
Section: Introductionmentioning
confidence: 99%